Initiation Behavior in Negotiations: The Moderating Role of Motivation on the Ability–Intentionality Relationship. (29th January 2013) - Volkema, Roger; Kapoutsis,, Ilias; Nikolopoulos, Andreas
Abstract This article reports on a study of the effects of recognition of negotiable opportunities (ability) and self‐efficacy (motivation) on initiation behavior in negotiations, an often overlooked stage of the negotiation process. Three phases of the initiation process are examined—engaging, requesting, and optimizing—through three negotiation scenarios offering corresponding forced‐choice behavioral options. Results suggest that, overall, the recognition of negotiable opportunities and the interaction of recognition and self‐efficacy best predict initiation intentionality. More specifically, recognition and the interaction of recognition and self‐efficacy were significantly associated with the likelihood of making a request, whereas the interaction of recognition and self‐efficacy was significantly associated with the likelihood of optimizing that request. The implications of these findings for practitioners and future research are discussed.